2014
DOI: 10.1371/journal.pone.0107308
|View full text |Cite|
|
Sign up to set email alerts
|

Establishment of Trophoblast Stem Cells under Defined Culture Conditions in Mice

Abstract: The inner cell mass (ICM) and trophoblast cell lineages duet early embryonic development in mammals. After implantation, the ICM forms the embryo proper as well as some extraembryonic tissues, whereas the trophoectoderm (TE) exclusively forms the fetal portion of the placenta and the trophoblast giant cells. Although embryonic stem (ES) cells can be derived from ICM in cultures of mouse blastocysts in the presence of LIF and/or combinations of small-molecule chemical compounds, and the undifferentiated pluripo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
88
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(96 citation statements)
references
References 28 publications
8
88
0
Order By: Relevance
“…The rapid decrease in Eomes levels with 25 ng/ml FGF2 does not appear to be a result of differentiation, as its abundance was constant for the duration of the experiment and no morphological evidence of differentiation was observed after 6 D in culture, whereas differentiated cells were readily observed at ≤2.5 ng/ml FGF2. These data suggest that FGF2 can support TSC maintenance, which is consistent with a recent report by Ohinata and Tsukiyama () indicating that FGF2 can be used to derive TSCs from mouse blastocysts.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The rapid decrease in Eomes levels with 25 ng/ml FGF2 does not appear to be a result of differentiation, as its abundance was constant for the duration of the experiment and no morphological evidence of differentiation was observed after 6 D in culture, whereas differentiated cells were readily observed at ≤2.5 ng/ml FGF2. These data suggest that FGF2 can support TSC maintenance, which is consistent with a recent report by Ohinata and Tsukiyama () indicating that FGF2 can be used to derive TSCs from mouse blastocysts.…”
Section: Resultssupporting
confidence: 92%
“…These observations suggest that in addition to its role in Genome-wide analysis of ERF DNA-binding sites in embryo fibroblasts (Twigg et al, 2013) identified a strong interaction of ERF with Fgf2. FGF signaling plays a pivotal role in TSC differentiation: FGF4 expressed by the inner cell mass is required for trophectoderm maintenance (Arman, Haffner-Krausz, Chen, Heath, & Lonai, 1998), while maintenance of murine TSCs requires FGF4 (Tanaka et al, 1998) or FGF2 (Ohinata & Tsukiyama, 2014). Attenuation of FGF2 signaling is also required for the differentiation of TSCs in humans (Sudheer, Bhusan, Fauler, Lehrach, & Adjaye, 2012).…”
Section: Erf May Contribute To Syncytiotrophoblast Lineage Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…However, hypomethylated patterns were unexpectedly found at the paternal allele in three of the four control TSC lines (TS-4, TS-5, and TS-6), ranging from 30.7% to 33.9%, although that of the SCNT-TSC lines remained hypermethylated (78.1% to 94.8%), probably in response to the SCNT procedure at this region (Table 1, Figure 4). We hypothesized that the reduction in DNA methylation at the paternal IG-DMR might have been caused by the use of serum-free conditioned medium (CDM) at their establishment [12], because it contains knockout serum supplement (KSR), known to induce hypomethylation of the IG-DMR in induced pluripotent stem cells (iPSCs) [13]. Thus, we next examined the IG-DMR of an additional series of TSCs (two IVF-TSC lines and three SCNT-TSC lines), which had been generated using the conventional TSC medium containing FGF4, heparin, and serum during the first 12-46 days of culture.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, a portion of the population of trophoblast cell lines maintains AP activity; however, the significance of this cell population is obscure in the trophoblastic cell lineage. Moreover, RT-PCR showed that these cells express trophoblast-specific genes, such as ELF5 , CDX2 , and SOX2 , which were also expressed in mouse TSCs [42, 43]. In addition, biTBCs express IFN-τ , an antiluteolytic factor responsible for preventing the regression of the maternal corpus luteum and supporting the sustainability of pregnancy for cattle uteri [7, 44].…”
Section: Discussionmentioning
confidence: 99%